Treatment with intravenous immunoglobulin increases the level of small EVs in plasma of pregnant women with recurrent pregnancy loss. (August 2020) - Jørgensen, Malene Møller; Bæk, Rikke; Sloth, Jenni; Varming, Kim; Christiansen, Ole Bjarne; Ditlevsen, Nadja Emilie; Rajaratnam, Nina
Highlights: Extracellular vesicles (EVs), which are small cell-derived compartments, take part in numerous different physiological processes. The contents of EVs reveal the cell of origin and indicates pathophysiological states in different diseases. In pregnancy disorders, changes have been reported in the composition, bioactivity and concentration of placental and non-placental EVs. In this study the contents of EVs were monitored in patient with recurrent pregnancy loss (RPL) when receiving intravenous immunoglobulin (IVIG) or placebo (albumin) treatment. Abstract: Extracellular vesicles (EVs), which are small cell-derived compartments, take part in numerous different physiological processes. The contents of EVs reveal the cell of origin and indicates pathophysiological states in different diseases. In pregnancy disorders, changes have been reported in the composition, bioactivity and concentration of placental and non-placental EVs. The purpose of this study was to monitor the effects on EVs in patients receiving intravenous immunoglobulin (IVIG) or placebo (albumin) treatment due to recurrent pregnancy loss (RPL). In a placebo-controlled trial study of IVIG treatment, plasma collected from 39 women with RPL were investigated using the Extracellular Vesicle Array (EV Array). Plasma was sampled consecutively (from gestational week (GW) 5) and the protein phenotypes of the smaller EVs (sEVs) were analyzed for the presence of 34 markers. The levels of sEVs or changes in their levels in early pregnancy were correlated with treatment. There was statistically significant increased levels of sEVs in patients who received IVIG versus placebo. In conclusion, the treatment with high-doses of IVIG clearly boosted the production and release of sEVs to the circulation; however, the biological role of this boost remains to be clarified in further studies.